Athletes are not at greater risk for death by suicide: A review - Pichler, E. M.; Ewers, S.; Ajdacic-Gross, V.; Deutschmann, M.; Exner, J.; Kawohl, W.; Seifritz, E.; Claussen, M. C. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Introduction Suicide represents a major mental and public health issue. Elite athletes share certain individual and environmental characteristics that may increase their risk for mental illnesses, ultimately leading to suicide. This notion conflicts with the general perception of athletes, being the healthiest representatives of society.